Corallopyronin A: antimicrobial discovery to preclinical development. Issue 9 (22nd June 2022) - Krome, Anna K.; Becker, Tim; Kehraus, Stefan; Schiefer, Andrea; Gütschow, Michael; Chaverra-Muñoz, Lillibeth; Hüttel, Stephan; Jansen, Rolf; Stadler, Marc; Ehrens, Alexandra; Pogorevc, Domen; Müller, Rolf; et al.
Abstract : Identifying new antibiotics and their further development is a priority of natural product research. The antibiotic corallopyronin A serves in this review as a show case for the development of a naturally occurring antibiotic compound. Abstract : Covering: August 1984 up to January 2022 Worldwide, increasing morbidity and mortality due to antibiotic-resistant microbial infections has been observed. Therefore, better prevention and control of infectious diseases, as well as appropriate use of approved antibacterial drugs are crucial. There is also an urgent need for the continuous development and supply of novel antibiotics. Thus, identifying new antibiotics and their further development is once again a priority of natural product research. The antibiotic corallopyronin A was discovered in the 1980s in the culture broth of the Myxobacterium Corallococcus coralloides and serves, in the context of this review, as a show case for the development of a naturally occurring antibiotic compound. The review demonstrates how a hard to obtain, barely water soluble and unstable compound such as corallopyronin A can be developed making use of sophisticated production and formulation approaches. Corallopyronin A is a bacterial DNA-dependent RNA polymerase inhibitor with a new target site and one of the few representatives of this class currently in preclinical development. Efficacy against Gram-positive and Gram-negative pathogens, e.g., Chlamydia trachomatis, Orientia tsutsugamushi, Staphylococcus aureus, and Wolbachia has been demonstrated. Due to its highly effective in vivo depletion of Wolbachia, which are essential endobacteria of most filarial nematode species, and its robust macrofilaricidal efficacy, corallopyronin A was selected as a preclinical candidate for the treatment of human filarial infections. This review highlights the discovery and production optimization approaches for corallopyronin A, as well as, recent preclinical efficacy results demonstrating a robust macrofilaricidal effect of the anti- Wolbachia candidate, and the solid formulation strategy which enhances the stability as well as the bioavailability of corallopyronin A.